Probing the inhomogeneity and intermediates in the photosensitized degradation of rhodamine B by Ag3PO4 nanoparticles from an ensemble to a single molecule approach. Issue 65 (22nd August 2017) - Xu, Beibei; Wang, Xiaojuan; Zhu, Chaofeng; Ran, Xia; Li, Tianfeng; Guo, Lijun
Abstract : This work reports the single-molecule observations of the photosensitized process and intermediates generation in the photodegradation of RhB by Ag3 PO4 nanoparticles. Abstract : The photoinduced dynamics related to the degradation of a surface adsorbate by a semiconductive catalyst is critical for understanding the photocatalytic mechanism and improving the catalytic property of nanoscale materials. Herein, we report the investigation of the inhomogeneous interactions between Ag3 PO4 nanoparticles and rhodamine B (RhB), and the direct observation of the intermediates generated in the photodegradation of RhB, using ensemble-averaged as well as single-molecule time-resolved fluorescence spectroscopies. The results demonstrate the existence of electron injection from RhB into the conduction band of Ag3 PO4 and the formation of a deethylation intermediate before the subsequent degradation process. The fluorescence diversity both in lifetime and intensity fluctuation indicates an inhomogeneous interfacial interaction between the RhB molecule and Ag3 PO4 nanoparticle with surface heterogeneity. Based on the lifetime distribution, the duration time of single-molecule events and the related dynamical analysis, it was revealed that the RhB molecule adsorbed on the active site of the Ag3 PO4 nanoparticle has a higher injection efficiency and better photocatalytic activity. Moreover, the lifetime evolution derived from a subsection of the single-molecule emission trajectories proved that the electron injection occurred prior to the degradation through the attack of free radical O2 ˙ − . These findings provide new insights into the heterogeneous interactions and dynamical information of the photosensitized degradation in an adsorbate/semiconductor catalyst.